An Exploratory Study on Spatial Governance Toward Urban–Rural Integration: Theoretical Analysis with Case Demonstration - Lin Tan; Qinyu Cui; Lan Chen; Lan Wang (Land)
Establishing a territorial space governance system that supports URI is essential for modernizing national governance capacity and systems. It also serves as a critical strategic measure to promote sustainable development in both urban and rural areas. The current research has not adequately explored the theoretical mechanisms and pathways of territorial spatial governance, resulting in challenges in providing the necessary theoretical foundations and practical guidance for advancing URI. The methods used in this study include theoretical analysis, logical deduction, and field research. The findings are as follows: (1) The key characteristics of TSG are the synergy of governance entities, the comprehensiveness of governance objects, the diversification of governance methods, and the systematization of governance content. Territorial spatial governance, driven by multiple stakeholders, influences the structure and functional arrangement of urban and rural territorial systems through means such as spatial planning, rights allocation, and top-level institutional design. (2) The essential process and core driving path to promote URI involve the interaction of urban and rural elements, the complementarity of their functions, and the reciprocity of their values, all guided by territorial space governance. (3) In the case study area, TSG facilitates the construction of an orderly element circulation channel, coordinating land circulation and capitalization, promoting local urbanization, and aligning residential with industrial development. This results in a complementary urban–rural functional structure, multifunctional rural development, and an urban–-rural model characterized by stable interest relationships and balanced service facility layouts.